Groundwater-surface water interactions at wetland interface: Advancement in catchment system modeling. (June 2022) - Rafiei, Vahid; Nejadhashemi, A.Pouyan; Mushtaq, Shahbaz; Bailey, Ryan T.; An-Vo, Duc-Anh
Abstract: Wetlands strongly interact with groundwater and surface water, influencing catchment hydrology and altering water quality. Meanwhile, catchment-scale models are typically unable to simulate groundwater-wetland interactions despite the fact that quantifying groundwater-wetland interactions can assist in better identifying locations for wetlands restoration/creation. We modified an integrated groundwater-surface water model (SWAT-MODFLOW-RT3D) to simulate water and nutrient exchange at the wetland interface. Several modifications were applied to the SWAT wetland module, and a spatial linkage was established between the module and the MODFLOW Drain Package to provide bidirectional water and nutrient exchange between groundwater and wetlands. We applied the modified model (SMR-W) to a tropical catchment in northeast Australia and quantified water and nitrate exchange between wetland, groundwater, and surface water for 28 potential locations. This study demonstrates that when groundwater heads are perched above wetlands bed, significant nitrate discharge from aquifers to wetlands occurs, which should be considered during wetland restoration planning. Graphical abstract: Image 1 Highlights: Wetlands are fully integrated into a groundwater and surface water model. The modified model helped with designing a catchment-scale wetland implementation plan. Wetland removal efficiency can vary considerably depending on the source of NO3 discharge.